An injectable chitosan/dextran/β -glycerophosphate hydrogel as cell delivery carrier for therapy of myocardial infarction. (1st February 2020) - Ke, Xiao; Li, Mingyan; Wang, Xiaoqing; Liang, Jiawen; Wang, Xing; Wu, Shaoyun; Long, Ming; Hu, Chengheng
Highlights: A thermosensitive injectable hydrogels developed as a promising cell delivery vehicle for cardiac cell therapy. Encapsulation of UCMSCs with CS/1.0 DEX/β-GP hydrogel can improve cell viability. The delivery of HUVECs from CS/1.0 DEX/β-GP hydrogel showed a linear-like profile. The prepared hydrogels could modulate the expression level of cTnI and Cx43 receptor of cardiac markers. A thermosensitive injectable hydrogels developed as a promising cell delivery vehicle for cardiac cell therapy. Encapsulation of UCMSCs with CS/1.0 DEX/β-GP hydrogel can improve cell viability. The delivery of HUVECs from CS/1.0 DEX/β-GP hydrogel showed a linear-like profile. The prepared hydrogels could modulate the expression level of cTnI and Cx43 receptor of cardiac markers. Abstract: Acute myocardial infarction (MI) is a common cardiovascular disease with high mortality. In this study, an injectable thermosensitive hydrogel of chitosan (CS)/dextran (DEX)/β–glycerophosphate (β-GP) loaded with umbilical cord mesenchymal stem cells (UCMSCs) was prepared for MI treatment. The good biocompatibility of hydrogels was confirmed by 3T3 cells and HUVECs culture study in vitro . HUVECs encapsulated in the hydrogels showed a cell delivery ability. Furthermore, the results indicated that hydrogel could encapsulate most of UCMSCs and the cells exhibited good viability in CS/ 1.0DEX/β-GP hydrogels. The expression of cardiac markers of cTnI and Cx43 and signaling pathways of p-Akt and p-ERK1/2 were studied, and it showed that UCMSCs differentiate towards myocardium and has a great potential for therapeutic use of cardiac repair. In conclusion, the thermosensitive hydrogel of CS/1.0 DEX/β-GP loaded UCMSCs was a promising candidate as cell delivery vehicle for cardiac repair to reconstitute damaged myocardium.